Differences in Taste Sensitivity between Vegans and Non-Vegetarians in Palembang, Indonesia - Takami Abbilardo; Shanty Chairani; Nursiah Nasution (Indonesian Dental Association, 2020)
Introduction: Many studies have shown that nutritional deficiencies can affect taste sensitivity. One group at high risk of nutritional deficiencies is vegans. Objective: The aim of the present study was to investigate the differences in taste sensitivity between vegans and non-vegetarians in Palembang, Indonesia. Methods: This was an observational analytic study with a quasi-experimental approach. A total of 60 subjects aged 21–45 years were included in this study. The subjects were divided into two groups: vegans (n = 30) and non-vegetarians (n = 30). Taste sensitivity was measured using the filter paper disc method. Five taste qualities (sweet, salt, sour, bitter, and umami) were tested using four different concentrations for each taste quality. The lowest concentrations identified correctly by the subjects were recorded as the taste sensitivity scores. The taste sensitivity scores were subsequently summed to form the taste scores. The data were analyzed using the Mann–Whitney U test. Results: The mean values of the sweet, bitter, and umami taste sensitivity scores and the taste score in the vegan group were lower than those in the non-vegetarian group. The mean value of the salt taste sensitivity score in the vegan group was higher than that of the non-vegetarian group, while the mean value in the sour taste sensitivity score was the same for both groups. There were no significant differences in the sweet, salt, sour, bitter, and umami taste sensitivity scores and taste scores of the vegan and non-vegetarian groups (p>0.05). Conclusion: The vegans and non-vegetarians in Palembang in this study have differences in taste sensitivity, but these results are not significant.